Physical component quality of life reflects the impact of time and moderate chronic kidney disease, unlike SF‐6D utility and mental component SF‐36 quality of life: An AusDiab analysis. Issue 6 (24th April 2019) - Wong, Muh G; Ninomiya, Toshiharu; Liyanage, Thaminda; Sukkar, Louisa; Hirakawa, Yoichiro; Wang, Ying; Wyld, Melanie L R; Morton, Rachel L; Chadban, Steven; Howard, Kirsten; Jardine, Meg J
ABSTRACT: Aim: Assessing the impact of interventions on the patient experience requires measures that are plausibly responsive to change. In a community cohort of people with and without chronic kidney disease (CKD) markers at baseline, we aimed to evaluate change in commonly used measures of quality of life (QOL) over the passage of 5 years. Methods: Included were 6400 participants in the Australian Diabetes, Obesity and Lifestyle (AusDiab) surveys with baseline and 5‐year CKD and QOL measures. Changes in SF‐6D utility, and the Medical Outcomes Study 36‐Item Short Form (SF‐36) physical (PCS) and mental (MCS) component summary scores, were evaluated with regression analyses according to the baseline presence of reduced estimated glomerular filtration rate (eGFR) (CKD‐Epidemiology Collaboration eGFR ≤60 m/min per 1.73 m 2 ) or albuminuria (urine albumin:creatinine ratio ≥3.4 mg/mmol). Results: At baseline, eGFR was reduced in 2.4% of participants and 5.1% had albuminuria. Participants with reduced eGFR had a lower SF‐6D and PCS, and those with albuminuria a lower PCS, compared with those without, but the differences were explained by known confounders. MCS scores were not affected by the presence of reduced eGFR or albuminuria. Over 5 years all groups exhibited stable SF‐6D and MCS scores but declining unadjusted PCS scores. PCS decline was greater for those with reduced eGFR, and remained significant after adjustment (−2.7 (−4.1 to −1.3) vs . −0.8 (−1.1 to −0.6, P  < 0.01). Analyses according to CKD stages were essentially unchanged. Conclusion: Utility and mental QOL appears stable over 5 years, unaffected by time or markers of CKD health. Physical QOL appeared to deteriorate with time, especially for those with CKD, making it a more likely candidate assessment measure for intervention and health service evaluations. Summary at a Glance: Based on Australian Diabetes, Obesity and Lifestyle (AusDiab) surveys with baseline and 5‐year chronic kidney disease (CKD) and quality‐of‐life (QOL) measures, the authors found that physical QOL deteriorates with time, especially for those with CKD, making it a more likely candidate assessment measure for intervention and health service evaluations.